Measurement of the integrated and differential t(t)over-bar production cross sections for high-p(T) top quarks in pp collisions at root s=8 TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (Physical Review D, 2016)
The cross section for pair production of top quarks (t¯t) with high transverse momenta is measured in pp collisions, collected with the CMS detector at the LHC with ffiffi s p ¼ 8 TeV in data corresponding to anintegrated luminosity of 19.7 fb−1. The measurement is performed using lepton þ jets events, where one top quark decays semileptonically, while the second top quark decays to a hadronic final state. The hadronic decay is reconstructed as a single, large-radius jet, and identified as a top quark candidate using jet substructure techniques. The integrated cross section and the differential cross sections as a function of top quark pT and rapidity are measured at particle level within a fiducial region related to the detector-level requirements and at parton level. The particle-level integrated cross section is found to be σt¯t ¼ 0.499 0.035ðstat þ systÞ 0.095ðtheoÞ 0.013ðlumiÞ pb for top quark pT > 400 GeV. The parton-level measurement is σt¯t ¼ 1.44 0.10ðstat þ systÞ 0.29ðtheoÞ 0.04ðlumiÞ pb. The integrated and differential cross section results are compared to predictions from several event generators.